Whole genome sequencing of multidrug-resistant Mycobacterium tuberculosis isolates collected in the Czech Republic, 2005-2020 - Dohál, Matúš; Dvořáková, Věra; Šperková, Miluše; Pinková, Martina; Spitaleri, Andrea; Norman, Anders; Cabibbe, Andrea Maurizio; Rasmussen, Erik Michael; Porvazník, Igor; Škereňová, Mária; Solovič, Ivan; Cirillo, Daniela Maria; et al. (Scientific reports, 2022)
The emergence and spread of resistant tuberculosis (TB) pose a threat to public health, so it is necessary to diagnose the drug-resistant forms in a clinically short time frame and closely monitor their transmission. In this study, we carried out a first whole genome sequencing (WGS)-based analysis of multidrug resistant (MDR) M. tuberculosis strains to explore the phylogenetic lineages diversity, drug resistance mechanisms, and ongoing transmission chains within the country. In total, 65 isolates phenotypically resistant to at least rifampicin and isoniazid collected in the Czech Republic in 2005-2020 were enrolled for further analysis. The agreement of the results obtained by WGS with phenotypic drug susceptibility testing (pDST) in the determination of resistance to isoniazid, rifampicin, pyrazinamide, streptomycin, second-line injectables and fluoroquinolones was more than 80%. Phylogenetic analysis of WGS data revealed that the majority of MDR M. tuberculosis isolates were the Beijing lineage 2.2.1 (n = 46/65; 70.8%), while the remaining strains belonged to Euro-American lineage. Cluster analysis with a predefined cut-off distance of less than 12 single nucleotide polymorphisms between isolates showed 19 isolates in 6 clusters (clustering rate 29.2%), located mainly in the region of the capital city of Prague. This study highlights the utility of WGS as a high-resolution approach in the diagnosis, characterization of resistance patterns, and molecular-epidemiological analysis of resistant TB in the country.
Keywords: mutace; Rifampin; Mycobacterium tuberculosis; Genotype; antituberkulotika; mikrobiální testy citlivosti; Whole Genome Sequencing; rifampin; lidé; genotyp; multirezistentní tuberkulóza; Mutation; Phylogeny; Microbial Sensitivity Tests; Tuberculosis; Tuberculosis, Multidrug-Resistant; Czech Republic; sekvenování celého genomu; isoniazid; tuberkulóza; mnohočetná bakteriální léková rezistence; Isoniazid; Česká republika; Drug Resistance, Multiple, Bacterial; Antitubercular Agents; fylogeneze; Humans